2005
DOI: 10.1108/02651330510630258
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the factors affecting the adoption of electronic commerce by SMEs

Abstract: Purpose -The study investigates the internet-based electronic commerce (EC) adoption profile of small and medium-sized enterprises (SMEs) in Turkey as well as the factors affecting their willingness to adopt EC usage. Design/methodology/approach -EC adoption is measured by a composite index of the usage frequency of 14 EC application tools. The study draws on the data obtained from a sample of 237 manufacturing SMEs with internet connection. Findings -In was discovered that EC adoption was significantly influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 21 publications
6
115
0
5
Order By: Relevance
“…Even the starting point of digitization, broadband access, has been shown to bring significant opportunities to SMEs such as reaching new target audiences, increasing performance and efficiency, and improving growth and competitiveness (Galloway, 2007;Shideler and Badasyan, 2012;Spurge and Roberts, 2005). In addition, internet use can benefit SMEs by reducing costs (Chong and Pervan, 2007;Kaynak et al, 2005;Lohrke et al, 2006) and facilitating both internal and external communication (Bharadwaj and Soni, 2007;Chong and Pervan, 2007;Eriksson, Hultman and Naldi, 2008;Kaynak et al, 2005). More recent developments in digitization, namely the social aspects of the web (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Even the starting point of digitization, broadband access, has been shown to bring significant opportunities to SMEs such as reaching new target audiences, increasing performance and efficiency, and improving growth and competitiveness (Galloway, 2007;Shideler and Badasyan, 2012;Spurge and Roberts, 2005). In addition, internet use can benefit SMEs by reducing costs (Chong and Pervan, 2007;Kaynak et al, 2005;Lohrke et al, 2006) and facilitating both internal and external communication (Bharadwaj and Soni, 2007;Chong and Pervan, 2007;Eriksson, Hultman and Naldi, 2008;Kaynak et al, 2005). More recent developments in digitization, namely the social aspects of the web (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Seyal et al (2004) conducted a study in Pakistan. Vaidya (2004, 2006) conducted studies in India, and Kaynak et al (2005) conducted a study in Turkey. All of these studies have given useful findings about E-commerce adoption in different national and cultural contexts (see table 3).…”
Section: Conceptual Modelling For E-commerce Adoptionmentioning
confidence: 99%
“…Several studies (Kaynak et al, 2005;Stockdale and Standing, 2004;Taylor and Murphy, 2004) have suggested that much of the literature related to web and e-commerce adoption has been undertaken in developed countries. They argue that directly transferring these findings to developing countries is not justifiable because the driving forces for firms' adoption of the web and e-commerce vary widely from location to location (Kartiwi and MacGregor, 2007).…”
Section: The Importance Of the Researchmentioning
confidence: 99%
“…Among the commonly cited barriers to web adoption are management's lack of awareness of the technology, security concerns, cultural barriers, problems in solving compatibility issues with existing IT system, lack of online payment process, difficulty of finding and training qualified personnel, lack of human interaction and lack of resources (Mavromatis and Buhalis,2003;Poon and Swatman, 1997;Khan, 2004;Dedrick and Kraemer, 2001;Kaynak et al, 2005;Bolongkikit et al, 2006, Taylor andMurphy, 2004).…”
Section: Internet Adoption By Smesmentioning
confidence: 99%
See 1 more Smart Citation